2019
DOI: 10.1186/s13643-019-1217-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lifetime substances use among students in Ethiopia: a systematic review and meta-analysis

Abstract: BackgroundThe use of substances is a growing concern in Ethiopia, and their impacts on younger generation have been a concern of different professionals. Even though students are at high-risk of substance abuse, there is lack of comprehensive evidence for policy decision on substance use among students. Therefore, the aim of this systematic review and meta-analysis was to estimate the prevalence of common substances among students in Ethiopia.MethodA comprehensive literature searches were done from biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
(134 reference statements)
6
6
2
Order By: Relevance
“…The current alcohol use prevalence in this study (22.9%) is higher than the result from Debre Berhan University (17%) but lower from Axum University (32.8%). 12,15,21,47,55 A slightly lower odds of lifetime alcohol use among female students observed in the current study (…”
Section: Substance Abuse: Research and Treatmentcontrasting
confidence: 42%
See 1 more Smart Citation
“…The current alcohol use prevalence in this study (22.9%) is higher than the result from Debre Berhan University (17%) but lower from Axum University (32.8%). 12,15,21,47,55 A slightly lower odds of lifetime alcohol use among female students observed in the current study (…”
Section: Substance Abuse: Research and Treatmentcontrasting
confidence: 42%
“…The current alcohol use prevalence in this study (22.9%) is higher than the result from Debre Berhan University (17%) but lower from Axum University (32.8%). 12 , 15 , 21 , 47 , 55 …”
Section: Discussionmentioning
confidence: 99%
“…Khat a substance that is structurally related to amphetamine was commonly consumed by students in the present study. Findings indicating high prevalence of khat use are similar to a systematic review that reported khat as one of the most consumed substances among university students in Ethiopia (56). Further, a meta-analysis indicated that the pooled prevalence of current khat use among university students was highest in Saudi Arabia (18.9%) followed by Ethiopia 13.6% and 13 % in Yemen (57).…”
Section: Discussionsupporting
confidence: 71%
“…Since 1980s, studies conducted across different parts of Ethiopia showed that the epidemiology of the use of the various substances; either as a single or concurrent use of any substance [27][28][29]. These studies predominantly focused on the lifetime use of substance among students and they tends to overestimate the prevalence and this was observed in our previous meta-analysis [30]. So far one meta-analyis focused on single substance but did not spacify whether the outcome was current or lifetime [31], and the other reported pooled prevalence of current khat chewing in serveral [32].…”
Section: Introductionmentioning
confidence: 97%